2017
DOI: 10.1016/j.copbio.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Rationalising vitamin B6 biofortification in crop plants

Abstract: Vitamin B encompasses a group of related compounds (vitamers) that can only be biosynthesised de novo by plants and microorganisms. Enzymatic cofactor and antioxidant functions for vitamin B are established in all kingdoms. Human vitamin B dietary insufficiency or genetic defects in B vitamer interconversion result in various neurological and inflammatory pathologies with several populations at-risk or marginal for vitamin B status. Three (rice, wheat and cassava) of the world's top five staple crops do not me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 58 publications
0
37
0
Order By: Relevance
“…Moreover, better education of smallholder farmers in China has been demonstrated to increase yields despite a reduction in nitrogen fertilizer (Cui et al, 2018), suggesting that better agronomy remains a feature that needs to be factored into models for optimized sustainable production. A number of studies have additionally demonstrated the feasibility of enhancing the levels of micronutrients and vitamins in plants both using conventional breeding and transgenesis (Harjes et al, 2008;Yan et al, 2010;Fudge et al, 2017;Vasconcelos et al, 2017), hinting that incorporating these traits into the parts list of an ideal crop may not represent an insurmountable hurdle.…”
Section: Current Challenges In Agriculturementioning
confidence: 99%
“…Moreover, better education of smallholder farmers in China has been demonstrated to increase yields despite a reduction in nitrogen fertilizer (Cui et al, 2018), suggesting that better agronomy remains a feature that needs to be factored into models for optimized sustainable production. A number of studies have additionally demonstrated the feasibility of enhancing the levels of micronutrients and vitamins in plants both using conventional breeding and transgenesis (Harjes et al, 2008;Yan et al, 2010;Fudge et al, 2017;Vasconcelos et al, 2017), hinting that incorporating these traits into the parts list of an ideal crop may not represent an insurmountable hurdle.…”
Section: Current Challenges In Agriculturementioning
confidence: 99%
“…Beyond the mainstream biofortification programmes for provitamin A, other studies have looked at biofortification in B vitamins. Vitamin B6 deficiency results in neurological and inflammatory pathologies involving increased risk of Parkinson's Disease, cancer, immune deficiencies, cardiovascular disease and high blood pressure (Fudge et al, 2017). Estimates of dietary deficiency for vitamin B6 run at 24% of US citizens, but 54% in Sudan and 64% in Uganda, perhaps because of the dietary dependency in Africa on vitamin B6deficient staple crops such as rice and maize.…”
Section: Biofortification Of B Vitaminsmentioning
confidence: 99%
“…Estimates of dietary deficiency for vitamin B6 run at 24% of US citizens, but 54% in Sudan and 64% in Uganda, perhaps because of the dietary dependency in Africa on vitamin B6deficient staple crops such as rice and maize. The RDA of vitamin B6 is 1.3-2 mg d À1 , although excessive consumption (9.6 mg d À1 ) has been associated with acute neuropathy (Fudge et al, 2017).…”
Section: Biofortification Of B Vitaminsmentioning
confidence: 99%
“…Mammals lack the ability to biosynthesize vitamin B 6 de novo , and plants represent one of their major sources of the vitamin (Fitzpatrick, ). Acute vitamin B 6 deficiency can lead to various chronic diseases in humans, including neurological disorders, cardiovascular disease, and diabetes (Hellmann and Mooney, ; Di Salvo et al ., ; Fudge et al ., ).…”
Section: Introductionmentioning
confidence: 97%